DESAIN dan IMPLEMENTASI APLIKASI PEMBELAJARAN BAHASA JEPANG - INDONESIA DENGAN METODE GAMIFICATION BERBASIS iOS - Adam Arif Budiman; Dwikky Mardianto (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2019)
Japanese is a foreign language that is widely studied in Indonesia. But in a large number of Japanese language students in Indonesia, there are still some problems that arise. As experienced by students at the University of Darma Persada who have difficulty in the process of learning Japanese itself. Difficulties experienced include, among others, Japanese grammar that is difficult to learn, letters that are difficult to understand, understanding the meaning of words and sentences in Japanese and others. This report contains research on making an application of Japanese-Indonesian learning with case studies on students at Darma Persada University. This application was created using the waterfall method, gamification method and design thinking method. This application is also created using the swift programming language and the Firebase data storage system and this application is applied to the iOS operating system.